Recent Advances in Synthesis and Properties of Nitrated-Pyrazoles Based Energetic Compounds - Zhang, Shijie; Gao, Zhenguo; Lan, Di; Jia, Qian; Liu, Ning; Zhang, Jiaoqiang; Kou, Kaichang (Molecules (Basel, Switzerland), 2020)
Nitrated-pyrazole-based energetic compounds have attracted wide publicity in the field of energetic materials (EMs) due to their high heat of formation, high density, tailored thermal stability, and detonation performance. Many nitrated-pyrazole-based energetic compounds have been developed to meet the increasing demands of high power, low sensitivity, and eco-friendly environment, and they have good applications in explosives, propellants, and pyrotechnics. Continuous and growing efforts have been committed to promote the rapid development of nitrated-pyrazole-based EMs in the last decade, especially through large amounts of Chinese research. Some of the ultimate aims of nitrated-pyrazole-based materials are to develop potential candidates of castable explosives, explore novel insensitive high energy materials, search for low cost synthesis strategies, high efficiency, and green environmental protection, and further widen the applications of EMs. This review article aims to present the recent processes in the synthesis and physical and explosive performances of the nitrated-pyrazole-based Ems, including monopyrazoles with nitro, bispyrazoles with nitro, nitropyrazolo[4,3-c]pyrazoles, and their derivatives, and to comb the development trend of these compounds. This review intends to prompt fresh concepts for designing prominent high-performance nitropyrazole-based EMs.